Effect of gas oil composition on performance parameters of the extractive desulfurization process. Issue 30 (7th March 2016) - Kumar, Sunil; Chandra Srivastava, Vimal; Kumar, Ashutosh; Nanoti, Shrikant Madhusudan
Abstract : Extraction of sulfur compounds reveal that sulfur removal from gas oil strongly depends on the molecular structure of the sulfur compound and composition of the carrier phase. Abstract : Extractive desulfurization of synthetic and actual gas oil with various solvents was carried out to understand the fruitfulness of studies on solvent screening using synthetic carrier phases. Solvent extraction of various model sulfur compounds from two synthetic carrier phases of different composition was carried out using N, N -dimethylformamide (DMF) solvent to illustrate the effect of the sulfur compound molecular structure on its extractability and interaction with the carrier phase composition. Removal of sulfur compounds from the synthetic carrier phase followed the order: BT ≈ DBT > 4-methyl-DBT > 3-methyl BT ≈ 4, 6-dimethyl-DBT > 2- N -octylthiophene ≫ 1-dodecanethiol. Thereafter, extraction of actual straight run gas oil (SRGO), cracked gas oil (CGO), and their mixtures was studied using DMF to understand the effect of their composition on extraction performance. Performance parameters such as yield of raffinate, degree of sulfur removal, distribution coefficient, and performance factor were found to be quite different for different gas oil streams. Thereafter, models were developed for correlating performance of extraction in terms of degree of sulfur removal ( D sr ), yield ( Y ) of extracted gas oil with composition of gas oil and operating conditions. A performance factor ( P f, α ) (defined as the summation of D sr and Y with the weight factor ( α ) to D sr ) model was used to estimate the optimum operating conditions to maximize the extraction performance. Results indicate that the value of the weight factor ( α ) affects operating conditions, D sr and Y, significantly and should be chosen with utmost care in light of downstream process capabilities and overall process economics.